Broad-band three dimensional nanocave ZnO thin film photodetectors enhanced by Au surface plasmon resonance. Issue 16 (13th April 2016) - Sun, Mengwei; Xu, Zhen; Yin, Min; Lin, Qingfeng; Lu, Linfeng; Xue, Xinzhong; Zhu, Xufei; Cui, Yanxia; Fan, Zhiyong; Ding, Yiling; Tian, Li; Wang, Hui; et al.
Abstract : A high-performance broadband photodetector was developed by combining 3D periodic nanocave structures and Au surface plasmon resonances. Abstract : ZnO semiconductor films with periodic 3D nanocave patterns were fabricated by the thermal nanoimprinting technology, which is promising for photodetectors with enhanced light harvesting capability. The Au nanoparticles were further introduced into the ZnO films, which boosts the UV response of ZnO films and extends the photodetection to visible regions. The best UV photoresponse was detected on the 3D nanocave ZnO–Au hybrid films, attributing to the light trapping mechanism of 3D periodic structures and the driving force of the Schottky barrier at the ZnO/Au interface, while the high visible photoresponse of ZnO–Au hybrid films mainly results from the hot electron generation and injection process over the Schottky junctions mediated by Au surface plasmon resonances. The work provides a cost-effective pathway to develop large-scale periodic 3D nanopatterned thin film photodetectors and is promising for the future deployment of high performance optoelectronic devices.